IMPACT OF THE APPENDICEAL POSITION ON THE DIAGNOSIS AND TREATMENT OF PEDIATRIC APPENDICITIS - Belén Aneiros Castro; Indalecio Can Novillo; Araceli García Vázquez; Pedro Yuste Garcia; Eduardo Ferrero Herrero; Andrés Gómez Fraile (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To investigate how symptoms vary according to the appendiceal position in pediatric patients and to demonstrate that the laparoscopic approach is safe and effective in any appendiceal location by comparing each location to another. Methods: The medical records of 1,736 children aged 14 or younger who underwent laparoscopic appendectomy over a period of 14 years were analyzed retrospectively. Patients were divided according to the position of the appendiceal tip into four groups: anterior, pelvic, retrocecal and subhepatic. The Kruskal-Wallis and chi-square tests were used with the Bonferroni correction, with a significant p<0.05. Results: The appendiceal location was anterior in 1,366 cases, retrocecal in 248 cases, pelvic in 66 cases and subhepatic in 56 cases. There were no significant differences between the groups in terms of patient age and gender. Abdominal pain was the only symptom with statistically significant differences between the groups. The rate of perforated appendicitis was higher in the subhepatic and pelvic positions. Intraoperative complications and conversions were not statistically significant. Technical difficulties and operative time were higher in subhepatic position. The rate of postoperative complications was similar between the different locations, except for bowel obstruction, which was higher in pelvic appendicitis. Conclusions: The clinical symptoms of appendicitis hardly ever change with the position of the appendix. The laparoscopic approach is safe and effective, regardless the appendiceal location.